Multiple drug resistance in hookworms infecting greyhound dogs in the USA. (December 2021) - Jimenez Castro, Pablo D.; Venkatesan, Abhinaya; Redman, Elizabeth; Chen, Rebecca; Malatesta, Abigail; Huff, Hannah; Zuluaga Salazar, Daniel A.; Avramenko, Russell; Gilleard, John S.; Kaplan, Ray M.
Abstract: Ancylostoma caninum is the most prevalent nematode parasite of dogs. We confirmed multiple-drug resistance (MDR) in several A. caninum isolates to all anthelmintic drug classes approved for the treatment of hookworms in dogs in the USA. Cases of MDR hookworms appear to be highly overrepresented in greyhounds. The aims of this study were to evaluate the drug-resistant phenotypes and genotypes of the A. caninum infecting greyhounds. Fecal samples from greyhounds of the USA were acquired from two greyhound adoption kennels, one active greyhound racing kennel, and three veterinary practices. Fecal egg counts (FECs) were performed on fecal samples from 219 greyhounds, and despite treatment with anthelmintics, the mean FEC was 822.4 eggs per gram (EPG). Resistance to benzimidazoles and macrocyclic lactones were measured using the egg hatch assay (EHA) and the larval development assay (LDA), respectively. We performed 23 EHA and 22 LDA on either individual or pooled feces, representing 54 animals. Mean and median IC50 and IC95 values for the EHA were 5.3 μM, 3.6 μM, and 24.5 μM, 23.4 μM, respectively. For the LDA, the median IC50 value was >1000 nM. These values ranged 62–81 times higher than our susceptible laboratory isolate. Only post-treatment samples were available. For samples collected <10 days post-treatment with albendazole, moxidectin, or a combination of febantel-pyrantel-moxidectin, the mean FEC were 349, 333, and 835 EPG, respectively. We obtained DNA from hookworm eggs isolated from 70 fecal samples, comprised of 60 individual dogs and 10 pools. Deep sequencing of the isotype 1 β-tubulin gene only revealed the presence of the F167Y (TTC>TAC) resistance polymorphism in 99% of these samples. These clinical, in vitro, and genetic data provide strong evidence that greyhound dogs in the USA are infected with MDR A. caninum at very high levels in prevalence and infection intensity. Graphical abstract: Image 1 Highlights: Conclusive evidence that most racing greyhounds in the USA are infected with MDR A. caninum. 79% of the samples from racing or retired greyhounds were positive. IC50 values for BZs and MLs were 62–81 times higher in greyhounds. The F167Y SNP was detected in 99% of samples, and in more than 2/3 the frequency was ≥ 75%.